PENGARUH BAHAN AJAR KETERAMPILAN BERBICARA TERHADAP KESANTUNAN BERBAHASA MAHASISWA UNIVERSITAS NEGERI MAKASSAR BERDASARKAN PERSPEKTIF LATAR PENDIDIKAN ORANG TUA - Fitri, Sakinah; Saleh, Muhammad; Jahrir, Andi Sahtiani (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Speaking skills and parental educational background are thought to have a strong influence on language politeness in daily communication. The speaking skills and educational background of parents in this study are intended to determine their effect on improving language politeness of Makassar State University students. This study used a pre-experimental method. The instrument used in the study was a test, namely pretest and postest. The results showed that the application of the speaking skills teaching material model can improve language politeness. The results of the second study indicate that the educational background of parents can influence the improvement of students' language politeness. Although, when compared to the increase in test results between groups of students with educational backgrounds of parents who graduated from S1, the effect was not significant.